Aswameda Sebagai Prosesi Ritual Berbalut Kuasa dalam Teks Aswamedaparwa - Duana Sutika, I Nyoman; Ngurah Sulibra, I Ketut (Humanis; Vol 28 No 4 (2024), 2024)
Research about Aswameda as a ritual procession wrapped in power in the text Aswamedaparwa this aims to expand social life in literary works related to power.   Rituals Aswameda in the text description he has not been punished is part of the great ceremony carried out by Yudistira in the text Aswamedapara as an effort to ask for forgiveness and atonement for the murder he committed against his relatives in the war Bharatayuda . This ritual is marked by the release of horses escorted by selected soldiers across other kingdom areas. Regions that recognize the authority of Hastinapura will allow horses to pass, whereas regions that try to block them will be resolved by war. Ritual procession Aswameda It looks like a show of power but it's true This ritual emphasizes alms primarily to clergy and other forms of ceremonial offerings. This research uses the literature study method which is directed at searching for data through documents that support the research process. The theories used are structural theory and reception theory. The results of this research will be a reflection of life in the form of traces of past culture reflected in literary works.